Some theological and philosophical influences configured by the theological principles of Johann Baptist Metz (Quaestiones Disputatae: temas en debate, 2017)
The article, framed in the context of a larger investigation, intends to give accountof those influences that formed what is known as the New Political theory, proposedby the theologian Johann Baptist Metz. Beginning with an analytical readingaccording to the stages of the historical development of this theology, it will showwhich are the evolutionary processes that the theological principles presentedas a critical reflection and as a world theology that sought the deprivitisation ofthe Christian faith and it’s position in the political experience through history.
Keywords: Ernst Bloch; Karl Rahner; Latin America; theology principle; Walter Benjamin